Analisis Framing Berita Korupsi di Media Online Tribun Medan - Nur Ainun Ghoisani Ritonga; Erwan Effendi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines the framing of corruption news in Tribun Medan online media during the 2024–2025 period using Robert N. Entman’s framing model. The research addresses how corruption is constructed through the dimensions of problem definition, causal interpretation, moral evaluation, and treatment recommendation. Employing a qualitative descriptive design, data were collected through news text documentation and in-depth interviews with the Law and Criminal Editor of Tribun Medan to strengthen data validity through source triangulation. The findings reveal that Tribun Medan frames corruption not merely as a legal issue involving state financial losses but also as a social problem affecting public rights and religious facilities. The identified causes emphasize systematic planning manipulation and weak oversight in strategic infrastructure projects. Moral evaluations are articulated through representations of public concern and social accountability toward perpetrators, while recommended solutions focus on judicial transparency and institutional reform within the bureaucracy. The study’s novelty lies in its integration of textual framing analysis with editorial perspectives to explain how a local online news outlet constructs corruption narratives within the socio-cultural context of North Sumatra. The findings indicate that Tribun Medan performs a watchdog journalism function by fostering public awareness and reinforcing collective social responsibility regarding corruption issues.